Tidal and environmental modulation of seismic noise at Mefite d’Ansanto (Italy) non-volcanic CO2 emission field - Petrosino, Simona; Dumont, Stéphanie; Morabito, Simona; Cusano, Paola (Frontiers in Earth Science, 2026)
The Mefite d’Ansanto (Southern Apennines, Italy) is one of the largest non-volcanic CO2 emission areas worldwide, representing a unique natural laboratory for investigating the interactions between geofluid circulation and external forcing mechanisms. In this study, we analyzed continuous seismic noise recorded by three stations deployed around the vent area, with the aim of exploring the influence of external drivers on noise parameters. We applied a combination of multiple linear regression (MLR) and Singular Spectrum Analysis (SSA) to seismic noise attributes, specifically RMS amplitude and polarization (Rlen), in two frequency bands associated with the activity of the emission vents. Our results indicate that environmental variables (mainly wind, solar radiation, air temperature, and soil moisture) and tidal strain contribute to signal modulations (20%–30% of the variance) on semidiurnal to monthly time scales. We propose that meteorological and tidal processes, by inducing variations in the physical properties of the shallow crust (permeability, pore pressure, stress distribution), can affect both near-surface seismic noise sources as well as the dynamics of the deeper degassing system. These findings highlight the potential of seismic noise as monitoring tool for tracking external forcing mechanisms acting on geofluid systems.